Enhancing Vehicle Tracking Systems Using GPS - Zainab Naser Azeez (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Vehicle security and fleet management have become increasingly vital in response to the rising incidents of vehicle theft and transportation inefficiencies. Specific Background: GPS-based tracking systems offer real-time monitoring capabilities, yet many available solutions lack seamless integration with communication modules for efficient user interaction. Knowledge Gap: Despite advancements, limited attention has been given to systems that autonomously authenticate user requests and transmit location data directly to mobile interfaces via GSM and Android applications. Aims: This study proposes a GPS-based vehicle tracking system that integrates GPS receivers, microcontroller processing, and GSM communication for real-time, user-initiated location tracking. Results: The developed system effectively captures GPS coordinates, verifies user identity via incoming calls, and transmits location data through SMS, which is subsequently mapped in an Android app. Novelty: Unlike conventional models, the proposed system disables GSM post-transmission and activates continuous GPS tracking, optimizing power usage and ensuring uninterrupted monitoring. Implications: The integration of GPS and GSM with intelligent control logic provides a cost-effective, user-friendly solution for real-time vehicle tracking, with potential applications in personal vehicle security, fleet logistics, and geofencing enforcement. Highlights: Integrates GPS and GSM for seamless real-time vehicle tracking. Uses caller authentication to initiate secure location sharing. Automatically switches modules to optimize power efficiency. Keywords: GPS, Vehicle Tracking, Real-Time Monitoring, Geofencing